Is mirror therapy all it is cracked up to be? Current evidence and future directions. - Moseley, G; Gallace, A; Spence, C (2008)
Despite widespread support of mirror therapy for pain relief in the peer-reviewed [2,4,12,19,23,24,25,30,33,35], clinical (e.g. [20] (and popular (e.g. [5]) literature, the overwhelming majority of positive data comes from anecdotal reports, which constitute weak evidence at best. Only two well described and robust trials of mirror therapy in isolation exist, on the basis of which we conclude that mirror therapy per se, is probably no better than motor imagery for immediate pain relief, although it is arguably more interesting and might be helpful if used regularly over an extended period. Three high quality trials indicate positive results for a motor imagery program that incorporates mirror therapy, but the role of mirror therapy in the overall effects is not known. Obviously, more robust clinical trials and experimental investigations are still required. In the meantime, the relative dominance of visual input over somatosensory input suggests that mirrors might have utility in pain management and rehabilitation via multisensory interactions. Indeed, mirrors may still have their place in pain practice, but we should be open-minded as to exactly how. © 2008 International Association for the Study of Pain.